Triplet-Triplet Annihilation Based Energy Upconversion Mechanism: Cyanine7 Dye Doped with Super Yellow and Rubrene Hosts - Murat Aydemir (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this work, two case studies forenergy upconversion mechanisms are presented; one via two photon absorption and the other one via triplet fusion mechanism. These are strongly requiredphotophysical mechanisms in conjugated organic molecules, due to showingability to enhance the efficiency of organic electronic devices. During theinvestigations, Cyanine7 (Cye7) molecule is used as a sensitizer and for thehost molecules rubrene and super yellow molecules are preferred due to their comparativelyclose locally excited triplet energy levels. The results show that upconverteddelayed fluorescence arises from triplet-triplet annihilation mechanism in thoseparticular sensitizer-host systems which gives rise to enhance the internalquantum efficiencies by populating the locally excited singlet states.Consequentially, for the first time Cye7 (near infrared) dye is used as asensitizer in an energy upconversion experiment, and also two photon absorptionmechanism is reported in ppv based 'super yellow' polymer which has two photonabsorption cross-section at 780 nm